Socioeconomic reconversion of post-mining territories: stakeholder engagement in mine closure processes - Silva Barreto, Rodrigo (2025)
Mining activity, especially in vulnerable contexts, fails to convert economic gains into sustainable development for post-mining, intensifying social impacts upon mine closure. This research argues that an integrative approach involving stakeholders through engagement and social dialogue appears as an alternative in understanding the territory's trajectory and establishing governance that is sustainable in the long term. The main aim of this work is to systematize a set of analytical categories aimed at strengthening engagement processes applied to the mine closure process. The chosen research strategy was indirect documentary research, which seeks articles and academic productions that support the exposed content. The academic literature is still relatively incipient when studying the themes related to social issues in mine closure and post-closure processes. It is also highlighted that effective participation will only occur when the impacted communities participate in the discussions and decision-making processes related to the present and future use of the territories.